Systematic Literature Review (SlR): Characteristics of Millennial Generation Workers - Supriyani, Ani; Yuwana, Yohana Koronka Adi; Lidya, Fatikha Putri; Sahrah , Alimatus (Jurnal Indonesia Sosial Sains, 2025)
This study examines the characteristics of millennial workers in Indonesia, focusing on their values, challenges, and needs within a constantly evolving work environment. Millennials, born between 1981 and 1996, are known as "digital natives" and tend to prioritize passion and meaning in their work over mere performance. They often question whether organizations value their contributions and provide opportunities for growth. Despite their high adaptability and leadership potential, millennials display low levels of commitment and loyalty, influenced by factors such as unsupportive work environments and negative perceptions of their generation. This research employs a systematic literature review (SLR) approach to summarize relevant findings, identify the challenges faced by millennials, and highlight the importance of responsive human resource management practices. By understanding the characteristics and needs of millennials, organizations are expected to enhance employee engagement, job satisfaction, and retention, as well as effectively leverage their potential within the workplace.